Pengaruh Experiential Marketing, Emotional Value, dan Cost Value Terhadap Loyalitas Pelanggan Kopi Se-Indonesia Surabaya - Susanto, Priscillia Sieny; Chandra, Chelsy; Oktavio, Adrie (Ranah Research : Journal of Multidisciplinary Research and Development, 2026)
This study examines the effect of experiential marketing, emotional value, and cost value on customer loyalty at Kopi Se-Indonesia Surabaya. The study used a quantitative cross-sectional method, with data collected through an online survey distributed to 160 customers who had made at least two purchases within the past year. The relationships between variables were analyzed using the PLS-SEM method with SmartPLS 4. The results show that experiential marketing has a significant positive effect on both emotional value and cost value. This suggests that the experiences customers have at the coffee shop contribute to how they perceive the value they receive. In addition, emotional value and cost value were found to significantly influence customer loyalty. Customers who feel comfortable, enjoy the atmosphere, and perceive the price as reasonable compared to the benefits received tend to show stronger loyalty toward the brand. These results highlight the importance of creating a positive in-store experience, including a comfortable environment and good interaction between staff and customers. This research enriches the literature on experiential marketing, emotional value, and cost value in the coffee shop industry, particularly among young consumers. Practically, the findings suggest that coffee shop businesses should focus on maintaining consistent customer experiences while ensuring that price, product quality, and service remain aligned to encourage long-term customer loyalty.